PENGARUH KOMPETENSI GURU DAN FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR PADA MATA PELAJARAN IPS SISWA KELAS VIII SMP NEGERI 1 KAPONGAN TAHUN PELAJARAN 2017/2018 - Nursalam Nursalam; Insiyah Insiyah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2018)
The purpose of this study was to determine the effect of teacher competence and learning facilities on learning achievement in IPS subjects for class viii junior high school 1 Kapongan students in the 2017/2018 academic year. This type of research is ex-post facto research. The subjects of this study were students of SMP Negeri 1 Kapongan in the 2017/2018 academic year who received social studies subjects with a population of 127 students. The data collection techniques in this study were a questionnaire, interview (interview) and documentation. Data analysis in this study was analyzed in each data collection technique. The results of this study indicate that there is a positive and significant influence between teacher competence on social studies learning achievement. The results of the analysis using simple regression obtained a correlation coefficient (rx1y) of 0.659 and a coefficient of determination (r2x1y) of 0.435. The t test was carried out and the t-test price was 6.073 and the t-table value was 1.675 at the 5% significance level, which means that t count was greater than t table and the effect of teacher competence on social studies learning achievement was significant. The results of this study indicate that there is a positive and significant effect of learning facilities on social studies learning achievement. The results of the analysis using simple regression obtained a correlation coefficient (rx2y) of 0.558 and a coefficient of determination (r2x2y) of 0.312. The results of this study indicate that there is a positive and significant influence on teacher competence and learning facilities together on social studies learning achievement. The results of the analysis using multiple regression obtained the correlation coefficient Ry (1.2) of 0.709 and the coefficient of determination R2 y (1.2) of 0.503. This shows that there is a positive and significant influence on the competence of teachers and learning facilities together on social studies learning achievement.